National toxicovigilance for pesticide exposures resulting in health care contact – An example from the UK's National Poisons Information Service. (June 2014) - Perry, L.; Adams, R. D.; Bennett, A. R.; Lupton, D. J.; Jackson, G.; Good, A. M.; Thomas, S. H. L.; Vale, J. A.; Thompson, J. P.; Bateman, D. N.; Eddleston, M.
Abstract Background. Although there are extensive systems in place for pharmacovigilance, similar systems for detecting adverse health effects relating to pesticide exposure are rare. In 2004, the National Poisons Information Service (NPIS) pesticide surveillance study was implemented to identify cases requiring health care contact in the UK. This report describes the epidemiology of pesticide exposures reported to poison centres in the UK over a 9-year period. Methods. Data on exposures were gathered through monitoring access to the NPIS's online clinical toxicology database TOXBASE® and through monitoring calls to the four NPIS units (Edinburgh, Cardiff, Newcastle and Birmingham). Severity was judged by both caller and NPIS staff. Results. During the 9 years, 34, 092 enquiries concerning pesticides were recorded; 7, 804 cases of pesticide exposure were derived from these enquiries. Exposures were predominantly unintentional and acute (6, 789; 87.0%); 217 (2.8%) and 755 (9.7%) were chronic unintentional and acute deliberate self-harm exposures, respectively. The majority of cases occurred in children, especially the 0–4 year age group The minimum incidence of pesticide exposure requiring health care contact was 2.0 cases/100, 000 population per year. Reported numbers were 6- to 25-fold greater than those picked up through other UK pesticide toxicovigilance schemes. There were 81 cases of severe toxicity and 38 cases of fatal exposure. Deliberate self-harm accounted for 62.3% of severe cases and 79% of deaths. Aluminium phosphide, paraquat, diquat and glyphosate were responsible for most severe and fatal cases. Conclusions. The data gathered from this pesticide surveillance study indicate that poison centre resources can usefully monitor pesticide exposures resulting in health care contact in the UK. The NPIS may usefully be one component of the UK's response to European legislation requiring surveillance of complications resulting from pesticide use.